Dietary intake of fats and fatty acids in the Korean population: Korea National Health and Nutrition Examination Survey, 2013 - Baek, Y., Osong Health Technology Administration Complex, Cheongju, Republic of Korea; Hwang, J.Y., Sangmyung University, Seoul, Republic of Korea; Kim, K., Dankook University, Cheonan, Repulbic of Korea; Moon, H.K., Dankook University, Yongin, Republic of Korea; Kweon, S., Osong Health Technology Administration Complex, Cheongju, Republic of Korea; Yang, J., Osong Health Technology Administration Complex, Cheongju, Republic of Korea; Oh, K., Osong Health Technology Administration Complex, Cheongju, Republic of Korea; Shim, J.E., Daejeon University, Daejeon, Republic of Korea (Nutrition research and practice, 2015)
BACKGROUND/OBJECTIVES: The aim of this study was to estimate average total fat and fatty acid intakes as well as identify major food sources using data from the Korea National Health and Nutrition Examination Survey (KNHANES) VI-1 (2013). SUBJECTS/METHODS: Total fat and fatty acid intakes were estimated using 24-hour dietary recall data on 7,048 participants aged ¡Ã 3 years from the KNHANES VI-1 (2013). Data included total fat, saturated fatty acid (SFA), monounsaturated fatty acid (MUFA), polyunsaturated fatty acid (PUFA), n-3 fatty acid (n-3 FA), and n-6 fatty acid (n-6 FA) levels. Population means and standard errors of the mean were weighted in order to produce national estimates and separated based on sex, age, income, as well as residential region. Major food sources of fat, SFA, MUFA, PUFA, n-3 FA, and n-6 FA were identified based on mean consumption amounts of fat and fatty acids in each food. RESULTS: The mean intake of total fat was 48.0 g while mean intakes of SFA, MUFA, PUFA, n-3 FA, and n-6 FA were 14.4 g, 15.3 g, 11.6 g, 1.6 g, and 10.1 g, respectively. Intakes of MUFA and SFA were each higher than that of PUFA in all age groups. Pork was the major source of total fat, SFA, and MUFA, and soybean oil was the major source of PUFA. Milk and pork were major sources of SFA in subjects aged 3-11 years and ¡Ã 12 years, respectively. Perilla seed oil and soybean oil were main sources of n-3 FA in subjects aged ¡Ã 50 years and aged 50 years, respectively. CONCLUSIONS: Estimation of mean fatty acid intakes of this study using nationally represented samples of the Korean population could be useful for developing and evaluating national nutritional policies.